Prerequisites for a computational approach to Minoan chronology - Panagiotopoulos, Diamantis; Trognitz, Martina (Archaeometry, 2025)
The paper examines the development, adoption, and limitations of the relative chronology system for Minoan pottery, initially established by Sir Arthur Evans and Duncan Mackenzie during the excavation of Knossos (1900-1906). Despite its weaknesses, this system remained largely unchanged due to its convenience rather than its accuracy. The study discusses adaptations of this framework, critiques its shortcomings - particularly in obscuring temporal variability - and explores alternative approaches, including computational methods and Linked Open Data (LOD). The proposed solution involves replacing rigid periodizations with a more precise system based on synchronisms, visualized through Gantt charts, and integrating regional sequences using mathematical modeling. The goal is to enhance chronological accuracy in Minoan archaeology, especially for critical transitional periods.